Ion-induced electron emission from Clean metals - Baragiola, R. A.; Alonso, E. V.; Ferrón, J.; Oliva-Fiorio, A. (North Holland Publishing Co., 1979)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina